The stridulatory organ in Opetiidae and Phoridae (Diptera) and phylogenetic implications for the evolution of higher flies - Brian V. Brown; Dalton de Souza Amorim (Scientific Reports, 2023)
Abstract Stridulatory sound-making organs evolved in a group of flies—the family Phoridae—by modifications of the microstructure of foreleg segments present in the shared ancestor of the clade (Phoridae + Opetiidae). The opetiids are the only group amongst the lower Cyclorrhapha in which plausible homologous structures could be found, though in a less derived condition. On the forefemur of Opetia there are numerous elongate, flattened microtrichia that in basal phorids are organized into a curved linear group (the scraper) which are scraped against a curved, ridged carina on the forecoxa (the file). The file was possibly derived from an extremely unusual set of three setae that have transverse sculpturing and sockets that limit lateral motion, and which are distributed across the opetiid forecoxa. In some phorid lineages, these setae seem to be fused into the forecoxa forming the linear ridged surface against which the scraper on the forefemur could be moved. The relationship between opetiids and phorids dates back to the Cretaceous, and this pattern of file and scraper can be clearly seen in some 100 mya Myanmar amber phorid fly fossils. These structures shared between opetiids and phorids suggest that these two families may be sister groups amongst the Platypezoidea. Different modifications of the forelegs of other higher flies may have similar roles.